2017
DOI: 10.3390/ijgi6030085
|View full text |Cite
|
Sign up to set email alerts
|

User-Generated Geographic Information for Visitor Monitoring in a National Park: A Comparison of Social Media Data and Visitor Survey

Abstract: Abstract:Protected area management and marketing require real-time information on visitors' behavior and preferences. Thus far, visitor information has been collected mostly with repeated visitor surveys. A wealth of content-rich geographic data is produced by users of different social media platforms. These data could potentially provide continuous information about people's activities and interactions with the environment at different spatial and temporal scales. In this paper, we compare social media data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
123
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(127 citation statements)
references
References 34 publications
(21 reference statements)
3
123
0
1
Order By: Relevance
“…It contains rich spatiotemporal information generated by the human sensors and provides a way to explore and understand the socio-economic conditions of a place [26,27]. Though there have been concerns regarding information bias and lack of standard quality control, several studies have empirically revealed that VGI is of equally good quality as authoritative data [8,28,29]. Several researchers have used VGI resources including geo-tagged contents (e.g., tweets and photos) [16][17][18]30], check-in data [18,30], OSM [31] and so on.…”
Section: Volunteered Geographic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains rich spatiotemporal information generated by the human sensors and provides a way to explore and understand the socio-economic conditions of a place [26,27]. Though there have been concerns regarding information bias and lack of standard quality control, several studies have empirically revealed that VGI is of equally good quality as authoritative data [8,28,29]. Several researchers have used VGI resources including geo-tagged contents (e.g., tweets and photos) [16][17][18]30], check-in data [18,30], OSM [31] and so on.…”
Section: Volunteered Geographic Informationmentioning
confidence: 99%
“…As a boon from the current "Information Age", a massive amount of data is now available via digital technologies and novel data sources [7]. Recent studies have demonstrated that new data sources such as social media can provide more insights in addition to the results from traditional surveys [8]. Paid and free data from online social media sources and remote sensing cater near-real-time data.…”
Section: Introductionmentioning
confidence: 99%
“…Research has mainly focused on geotagged data from photo-sharing websites such as Flickr and Instagram (no longer available for download). Such data had been used to quantify recreation at natural and cultural sites at a global scale [12], model visitation rates in national parks [20], measure parks' popularity [21], map visitor flows [22,23], identify factors contributing to distribution patterns [11,24], and measure visitor use and spatial patterns [25]. Furthermore, data from web-share services, such as Wikiloc and GPSies, had been used to measure the intensity of use for mountain biking in natural environments [26] and to compare data sources for assessing visitation to parks [27].…”
mentioning
confidence: 99%
“…Furthermore, data from web-share services, such as Wikiloc and GPSies, had been used to measure the intensity of use for mountain biking in natural environments [26] and to compare data sources for assessing visitation to parks [27]. Nevertheless, further research on the applicability and validity of social media data as a source of information for visitor monitoring is needed [25].We contribute to the literature by providing an exploratory analysis of the time-based component of geotagged data with three different time measurements; monthly, weekly, and daily, and how well this new source of data matched official visitor data. Several papers in the literature have demonstrated the usefulness of crowdsourced data for behavioral study purposes.…”
mentioning
confidence: 99%
“…Furthermore, Zhang et al [23] analyse a theme park's tourism-carrying capacity (TCC) and devise a conceptual framework that categorizes determinants of TCC on three levels as fundamental, mediating, and direct determinants. To conduct the research, data was collected from questionnaires, social media [24] or publicly accessible databases. The authors in other studies used regressions models [13,25] of visitor numbers.…”
Section: Introductionmentioning
confidence: 99%